Optimization of process parameters in Electric Discharge Machining Process of Ti-6Al-4V alloy using hybrid Taguchi based MOORA method. Issue 1 (February 2021) - Srikanth, R; Singaravel, B; Vinod, P; Aravind, S; Subodh, D
Abstract: Electric Discharge Machining (EDM) process is used where the materials are difficult to machine by conventional methods. Titanium alloy is extensively used in aerospace industries because of its light weight and strength. This titanium alloy can be grouped into hard to cut materials and EDM is preferred for machining. In this work, an attempt is made by machinability analysis of titanium alloy on EDM using non-treated, cryogenically treated and tempered conditioned copper electrodes. The input parameters chosen are current, pulse on time, pulse off time and electrodes with different conditions. The output parameters are investigated include Material Removal Rate (MRR) and Tool Wear Rate (TWR). Taguchi based Multi Objective Optimization Ratio Analysis (MOORA) is used to find value of optimum input and output parameters. The result showed that cryogenically treated with tempered copper electrodes are good in machining performance and proposed Taguchi bases MOORA method has capable of solving multiple objectives simultaneously.